1998
DOI: 10.1038/sj.bjp.0701872
|View full text |Cite
|
Sign up to set email alerts
|

KATP‐channel activation: effects on myocardial recovery from ischaemia and role in the cardioprotective response to adenosine A1‐receptor stimulation

Abstract: 1 Optimization of myocardial energy substrate metabolism improves the recovery of mechanical function of the post-ischaemic heart. This study investigated the role of K ATP -channels in the regulation of the metabolic and mechanical function of the aerobic and post-ischaemic heart by measuring the e ects of the selective K ATP -channel activator, cromakalim, and the e ects of the K ATP -channel antagonist, glibenclamide, in rat fatty acid perfused, working hearts in vitro. The role of K ATP channels in the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Pacing could not resolve this question as there was no recovery of AO in control paced hearts. Most studies that have demonstrated a cardioprotective effect of A 1 receptor activation have applied the agonist prior to ischaemia (Mentzer et al ., 1993; Ford, Lopaschuk, Schulz & Clanahan, 1998), rather than during ischaemia and reperfusion as in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Pacing could not resolve this question as there was no recovery of AO in control paced hearts. Most studies that have demonstrated a cardioprotective effect of A 1 receptor activation have applied the agonist prior to ischaemia (Mentzer et al ., 1993; Ford, Lopaschuk, Schulz & Clanahan, 1998), rather than during ischaemia and reperfusion as in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…A similar cardiodepressant effect of the sulfonylurea glibenclamide was recently reported by Ford et al (1998), who subjected isolated working rat hearts to 30 min of global ischemia followed by 30 min of reperfusion. In the presence of 30 µmol/l glibenclamide, left ventricular work was markedly depressed during reperfusion as compared to hearts in the absence of glibenclamide.…”
Section: Effects Of Glibenclamidementioning
confidence: 61%
“…Indeed, animal models exist in which cardiodepressant effects of sulfonylureas have been demonstrated. For example, in isolated working rat hearts subjected to global ischemia followed by reperfusion, the ventricular work was significantly depressed by glibenclamide (Ferdinandy et al 1995;Ford et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Also Yao and Gross (44) demonstrated in in vivo dog hearts that glibenclamide abolished the protection against stunning afforded by the A 1 agonist CCPA. In contrast, Ford et al (10) found no inhibition of functional protection by glibenclamide in working rat hearts. However, the protocol of Ford et al and the Yao and Gross stunning protocol differ from ours and in crucial aspects.…”
Section: Glibenclamide Blocks Adenosine Cardioprotectionmentioning
confidence: 90%